Pendampingan Pengembangan Kapasitas Bisnis Usaha Mikro Kecil dan Menengah di Kota Tangerang Selatan - Anisa Fahmi; Trisulo Trisulo; Rahayu Kusumawati (Jurnal Nusantara Mengabdi, 2023)
Purpose: This activity aims to assistance to MSMEs in developing business capacity in the form of standardized financial reports. Methodology: The implementation of this activity is divided into three stages, mapping conditions, implementing activities, and strengthening business capacity. Interview and observation methods are used to identify partners' problems in developing businesses. Results: Through this community service, MSME partners better understand the importance of good financial reports. MSME partners conclude that the SME Accounting Application is easy to use to prepare simple financial reports, recording financial transaction data can be done practically through the application, and financial reports recorded in the SME Accounting application are more accurate and can minimize errors. We also advise MSME partners to improve product displays to make them more attractive to buyers. Conclusion: The knowledge of MSME in preparing financial reports according to standards increased and the SME Accounting Application is easy to use to prepare simple financial reports.